Electrostatic deposition of nanofibers for sensor application - Ana Neilde Rodrigues da Silva; Rogerio Furlan; Idalia Ramos; Jorge Juan Santiago-Avilés (Materials Research, 2005)
This work addresses the formation of nanofibers (with hundred of nanometers) by using electrospinning (electrostatic deposition) aiming at applications as sensors. Different quantities of a colloidal dispersion of graphite particles were blended with polyacrylonitrile (PAN) and N,N dimethylformamide (DMF), resulting in a series of solutions with carbon concentrations ranging from 0 to 25%. Precipitation was observed depending on the concentration of carbon added to the precursor blend. As a consequence, the relative viscosity decreases, due to PAN molecules removal from the solution by carbon particles adsorption, forming precipitates. The resulting fibers show an irregular shape, as observed by SEM and the diameters decrease with the increase of the carbon concentration in the precursor blend. The incorporation of carbon particles in the fibers was confirmed by FTIRS and Raman spectroscopy.